Association of physical activity on body composition, cardiometabolic risk factors, and prevalence of cardiovascular disease in the Korean population (from the fifth Korea national health and nutrition examination survey, 2008-2011) - Gwang-Sil Kim; Eui Im; Ji-Hyuck Rhee (BMC, 2017)
Abstract Background Data regarding associations among physical activity (PA) level, body composition, and prevalence of cardiovascular diseases in Asian populations are rare. Methods The International Physical Activity Questionnaire (IPAQ) was utilized to estimate PA levels and analyze the association of PA level with various body composition parameters and the prevalence of cardiovascular diseases by using data from the Korean National Health and Nutrition Examination Survey from 2008 to 2011. Results Moderate and high PA levels were associated with lower prevalence of hypertension and diabetes mellitus, and lower concentrations of serum ferritin, parathyroid hormone, and alkaline phosphatase. Sarcopenia (low vs. moderate vs. high PA group: 14.3% vs. 10.5% vs. 7.3%, p = 0.001), underweight (5.7% vs. 4.9% vs. 3.5%, p = 0.001), and central obesity (7.8% vs. 6.9% vs. 6.3%, p = 0.002) were more often observed in the low PA group. The prevalence rates of cardiovascular diseases were lower in the moderate (odds ratio [OR], 0.822; 95% confidence interval [CI], 0.737-0.916; p = 0.001) and high activity groups (OR, 0.663; 95% CI, 0.589-0.748; p = 0.001) than in the low activity group, even after adjusting for age, sex, smoking, underlying disease, and general or abdominal obesity and muscle mass. Conclusion Regular physical activity was associated with a low prevalence of cardiovascular diseases (stroke, myocardial infarction, stable angina, and chronic renal disease), which was independent of body composition and conventional risk factors in the Korean population, with a positive dose-response relationship.